2015
DOI: 10.1116/1.4929664
|View full text |Cite
|
Sign up to set email alerts
|

Vapor deposition on doublet airfoil substrates: Coating thickness control

Abstract: A combined simulation and experimental approach is used to investigate vapor deposition onto model doublet guide vane substrates found in gas turbine engines. These substrates contain surface regions that are not visible to the vapor source. Particular attention is given to coatings on interior surfaces of the doublet airfoil geometry, which are only accessible through the leading and trailing openings of the doublet airfoil substrate. Deposition of nickel is simulated for several flow conditions and vane sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The design of the two individual airfoils was identical to that previously used in an investigation of single airfoil deposition 15,16 and a study of coating thickness on a doublet guide vane. 25 During the simulations, the doublet airfoils were assumed perfectly two-dimensional (taken to have infinite length in the out of plane direction). For experiments, the airfoils were 31.75 mm high in the out of plane direction and were capped on each side by a thin backing plate [ Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The design of the two individual airfoils was identical to that previously used in an investigation of single airfoil deposition 15,16 and a study of coating thickness on a doublet guide vane. 25 During the simulations, the doublet airfoils were assumed perfectly two-dimensional (taken to have infinite length in the out of plane direction). For experiments, the airfoils were 31.75 mm high in the out of plane direction and were capped on each side by a thin backing plate [ Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1. 25 It is indicated that during vapor deposition onto a rotated guide vane substrate, the midregions of the interior convex and concave surfaces received a much smaller fraction of the evaporated flux than the outer surfaces, and led to significant disparities in coating thickness. The study in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, in addition to rotating and tilting actions, commercial EB-PVD chambers coat multiple blades in each batch [18]. of predicting vapour deposition have been discussed in the literature [7,[19][20][21][22]. Modelling of the degradation or failure mechanisms has also received attention [12,[23][24][25][26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%